Pengaruh Tipe Kelahiran terhadap Produksi Susu, Lama Laktasi, Masa Kering, Masa Kosong, dan Selang Beranak Kambing Saanen - Yudi; A. Atabany; B. P. Purwanto (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
The purpose of this research was to determine the effect of Saanen doe goats’ birth types on milk yields,lactation length, dry period, days open and kidding interval at PT Fajar Taurus. This research employeda case study method using secondary data of production and reproduction of Saanen doe goats. Datawas analysed using Microsoft Excel program and Kruskal Wallis test. The results showed percentages ofSaanen doe goats with single, twinning and triplets birth are 47.94%, 39.73% and 12.33% respectively.Milk yields for single birth was 1,14±0,43 litres/goat/day, lactation length of 286.43±119.73 days, dryperiod of 68.89±18.57 days, days open of 205.31±117.67 days, and kidding interval of 355.31±117.67days. Milk yields for twinning birth was 1.32±0.49 litres/goat/day, lactation length of 270±219.43 days,dry period of 69.10±17.52 days, days open of 189.10±227.22 days, and kidding interval of 339.10±227.22days. Meanwhile, milk yields for triplets birth was 0.93±0.40 litres/goat/day, lactation length of360±228.97 days, dry period of 66.67±23.78 days, days open of 276.67±240.38 days, and kidding intervalof 426.67±240.38 days. There is nonsignificant effect of birth types on milk yields, lactation length, daysopen and kidding interval in Saanen doe goats (P>0.05). However, birth types were found to have asignificant effect on dry period (P<0.05).